2022
DOI: 10.1136/bmj-2022-071476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral antimicrobial prophylaxis on surgical site infection after elective colorectal surgery: multicentre, randomised, double blind, placebo controlled trial

Abstract: Objective To investigate whether oral antimicrobial prophylaxis as an adjunct to intravenous antibiotic prophylaxis reduces surgical site infections after elective colorectal surgery. Design Multicentre, randomised, double blind, placebo controlled trial. Setting 11 university and non-university hospitals in France between 25 May 2016 and 8 August 2019. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…While this study might be underpowered, differences with the current study cohort could also be ascribed to a control arm without MBP and the single dose regimen used, perhaps not su cient to impact the gut microbiome. A French trial comprising colorectal resections compared ornidazole only versus placebo and found an SSI difference of 22 vs 13%, while the subset of patients with MBP had an even greater bene t from OAB [27]. While strengthening the hypothesis that OAB and MBP in combination are bene cial, in the current study clear SSI improvements were suggested only in the dual OAB group, which might be explained the admittedly weaker study design.…”
Section: Discussioncontrasting
confidence: 39%
“…While this study might be underpowered, differences with the current study cohort could also be ascribed to a control arm without MBP and the single dose regimen used, perhaps not su cient to impact the gut microbiome. A French trial comprising colorectal resections compared ornidazole only versus placebo and found an SSI difference of 22 vs 13%, while the subset of patients with MBP had an even greater bene t from OAB [27]. While strengthening the hypothesis that OAB and MBP in combination are bene cial, in the current study clear SSI improvements were suggested only in the dual OAB group, which might be explained the admittedly weaker study design.…”
Section: Discussioncontrasting
confidence: 39%
“…However, there is no consensus on the type and optimal dosage of antibiotics to be used. Futier et al have reported the SSI suppressive effect of a single 1000 mg dose of ornidazole in a multicentre, double‐blind, randomized trial [18]. Papp et al also conducted a prospective multicentre study and reported that preoperative oral administration of 1500 mg of MNZ and 3000 mg of neomycin can prevent SSI [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies on colorectal surgery have shown that the gut microbiome, whose composition and function are affected by antimicrobial prophylaxis, plays a major role in anastomotic healing 43,44 . A recent multicenter, double-blind, randomized trial investigating colorectal surgery (n=926) showed that enhanced anaerobic coverage in antimicrobial prophylaxis (addition of a single dose of ornidazole to cefoxitin) significantly reduced anastomotic leakage [relative risk, 0.59 (0.36–0.99)] as well as SSI [0.60 (0.45–0.80)] 8 . Although there would be a time lag between the use of antibiotic prophylaxis and the occurrence of anastomotic leakage, even single-dose antibiotics can reportedly change the composition of the gut microbiome for approximately 1 week 45,46 .…”
Section: Discussionmentioning
confidence: 99%